Energy-efficiency-oriented Gradient-based Economic Predictive Control of Multiple-Chiller Cooling Systems⁎We would like to thank the support by MINECO-Spain and FEDER Funds under project DPI2016-76493-C3-1-R. Issue 2 (2020) - Nadales, J.M.; Ordonez, Joaquin G.; Coronel, Juan F.; Limon, D.
Abstract: The growing use of air conditioning systems has become one of the main drivers of energy consumption in buildings. Many efforts are being made to develop new designs and control strategies to improve energy efficiency and minimise electricity consumption. In this work, a model for a case study of multiple-chiller-based cooling system is presented, based on surrogate models derived from information provided by manufacturers, and the study of the economic performance index. Then, an economic predictive control strategy will aim to operate the system optimizing the efficiency of the plant. Instead of the classical two-layer economic predictive control structure, where the reference to be tracked by the controller is given by a real-time optimizer, here we consider a single-layer control strategy where the gradients with respect to the manipulated inputs of the economic performance index are included in the cost function of the model predictive controller. The resulting optimization problem to be solved on line is a QP, which considerably eases the optimization problem, while also avoiding discrepancies between layers that could lead to loss of feasibility.